Water Treatment Performance of PAN/HPMC/Gr Nano Composites - Masar A. Akaood; Iftikhar M. Ali; Basma I. Waisi (Iraqi Journal of Physics)
This study investigates polyacrylonitrile:hydroxypropyl methylcellulose )PAN:HPMC( and PAN:HPMC: graphene (Gr) composite nanofibers prepared using the electrospinning technique. Electrospinning is a simple and versatile technique that relies on the electrostatic repulsion between surface charges to continuously draw nanofibers from a viscoelastic fluid. Membrane technology is vital in removing contaminants due to its easy handling and high efficiency. The results demonstrated that the Gr was successfully incorporated into the PAN:HPMC nanofiber membranes, as confirmed by scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) measurements. The Gr content has a significant impact on the diameter, porosity, and pore size. The PAN:HPMC:0.02Gr electrospun nanofiber membranes achieved excellent oil rejection (72.47%) and good permeability flux (750 LMH); this might be a result of how well the functional groups of the equally distributed Gr within the PAN:HPMC nanofibers interacted with oil. It was noticed that oil rejection dropped a lot as the Gr content went up. This is likely because the pores got wider and some of the Gr stacked or agglomerated across the nanofibers.